PERSPEKTIF HUKUM EKONOMI SYARIAH DALAM INVESTASI SAHAM SYARIAH DI BURSA EFEK INDONESIA - Muhammad Wahyudi; Dea Fani; Indah Pratiwi (Jurnal At-Tabayyun, 2021)
Investment and The sale and purchase of shares are still considered a speculative activity and is prohibited by religion because it is the same as gambling for ordinary people . To straighten this out , this study aims to analyze how Islamic stock investment in the Indonesia Stock Exchange from the perspective of Islamic economic law . The research method used is normative juridical with a qualitative approach . This research draws research sources from interviews with several investors and sharia economic law experts , then documents of laws and regulations , and literature studies related to research . The results show that investing and buying and selling of shares is halal and justified in the teachings of Islam , both Al - Qur'an , the Prophet's Hadith , Kaidah Fiqh , Ijma ' ulama , and the opinions of scholars . Then , from the perspective of sharia economic law , buying and selling or investing in shares for investment purposes is permitted , because buying and selling with underlying stocks is halal , even recommended because it fulfills investment and asset development of one of the maqasid sharia ( Hifdzul maal ) . In addition , stock transactions from the perspective of sharia economic law are assessed from the use of the contract . It is known that the contract used is Bai ' Al - Musawamah and the transaction refers to musyarakah or syirkah